Importância dos arranjos horizontais e competitividade para produtores de leite no Paraná - Brito, Marcel Moreira de (2014)
In this paper, the main objective was to determine whether dairy farmers participating in horizontal production arrangements have less asymmetric information and are more competitive than others producers who did not participate in these arrangements. The paper is composed of a general introduction containing the theoretical review, two articles and final considerations. The first article focuses on the asymmetry of information between farmers and dairy industry and in their productive activities. Considering the presupposition that higher access to information, result in fewer risky decisions in the production systems. So, the main objective of the first article was to determine whether producers participating in horizontal production arrangements in have lower information asymmetry facing those who do not participate. For the second article, the objective was to determine whether dairy farmers participating in horizontal production arrangements are more competitive compared to producers who do not participate. With the purpose to accomplish the objectives, in addition to literature review about the SAI milk in Brazil and Paraná and theoretical review on the New Institutional Economics ( NIE ) and Transaction Cost Economics (TCE) , semi-structured questionnaires were applied to 120 milk producers between the months of March 2012 and February 2013, in four geographic regions of Paraná: Central North, Central East, West and Southwest. The choice of these regions arises from the representation of the milk production in the state as well as the heterogeneity of production systems, which reflects the reality in the state. The collected data were tabulated and statistically analyzed using the Statistical Package for Social Sciences - SPSS version 18 for conducting multivariate analysis - Exploratory Factor Analysis (EFA) and t-student test. In the first article, statistical differences (P<0.05) were found between the group of producers who participated and who did not participate in horizontal arrangements, for the factors: "information about the transaction characteristics" and "comprehensive information about the activity". It was concluded that farmers who participate in horizontal arrangements are embedded in an environment of lower information asymmetry in its relations with industry and about productive issues; therefore represent the group with the lowest risk in the activity. The results of the second article indicated that producers who participate in horizontal arrangements had higher averages and statistically difference (P<0.05) for the factors "market relationship" and "productivity and technology", and for that reason they are more competitive, than those who did not participate in the horizontal arrangements. From the general results obtained in this paper, it was concluded that farmers who participate in horizontal arrangements have lower risk in the activity and are more competitive when compared to those that not participate.